ANALISIS DIAGNOSIS KESEHATAN KEPEMIMPINAN DI LEMBAGA DIKLAT - Dewi Utari Anggraen (Jurnal Tata Kelola Pendidikan, 2021)
Leadership in an organization has a major influence on achieving its goals. The main research question of this study was thus whether the leadership in the organization is running well. Hence, an instrument is required. That leads to why this author was interested in researching it with the title "An Analysis of Leadership Health Diagnostic Instruments in Training Institutes." This study aims to make an instrument of leadership health diagnostic that can be useful to determine the health category of each training institutes being observed. Besides, to overcome any issues in carrying out management functions. The method used in this study was a descriptive method with a quantitative approach. The study was conducted in the form of questionnaires, with data being gathered via google form. The sample of this study was the head centre, leaders at each division, field, and section as well as 165 employees from three training institutes, namely PPPPTK BMTI, PPPPTK IPA, and PPPPTK TK PLB. The technique used was a proportional stratified random sampling technique with calculations using the Taro Yamane or Slovin formula. Hence, the finding suggests that the three institutes are interpreted in the "healthy" category. This indicates that leadership activities and management functions have been well-conducted. Overall, the average calculation results of the general tendency are 3.54 or equal to 88.5.